A systematic review of colorectal multidisciplinary team meetings: an international comparison. Issue 3 (20th May 2021) - Fehervari, M; Hamrang-Yousefi, S; Fadel, M G; Mills, S C; Warren, O J; Tekkis, P P; Kontovounisios, C
Abstract: Background: Colorectal multidisciplinary teams (CR MDTs) were introduced to enhance the cancer care pathway and allow for early investigation and treatment of cancer. However, there are no 'gold standards' set for this process. The aim of this study was to review the literature systematically and provide a qualitative analysis on the principles, organization, structure and output of CR MDTs internationally. Methods: Literature on the role of CR MDTs published between January 1999 and March 2020 in the UK, USA and continental Europe was evaluated. Historical background, structure, core members, education, frequency, patient-selection criteria, quality assurance, clinical output and outcomes were extracted from data from the UK, USA and continental Europe. Results: Forty-eight studies were identified that specifically met the inclusion criteria. The majority of hospitals held CR MDTs at least fortnightly in the UK and Europe by 2002 and 2005 respectively. In the USA, monthly MDTs became a mandatory element of cancer programmes by 2013. In the UK, USA and in several European countries, the lead of the MDT meeting is a surgeon and core members include the oncologist, specialist nurse, histopathologist, radiologist and gastroenterologist. There were differences observed in patient-selection criteria, in the use of information technology, MDT databases and quality assurance internationally. Conclusion: CR MDTs are essential in improving the patient care pathway and should express clear recommendations for each patient. However, a form of quality assurance should be implemented across all MDTs.